Gambaran Pembelajaran dengan Metode Student Centered Learning pada Mata Kuliah Manajemen Keperawatan di Program Studi Sarjana Keperawatan: Studi Deskriptif Historis - Rejeki, Yunita Fitri; Nur Erawan, Annisa; Napitupulu, Indra Karana; Wahyudin, Tantowi Purnama (PT Karya Inovasi Berkelanjutan, 2025)
Introduction and Method Effective learning methods can enhance student engagement and accelerate the learning process. Among regular students who utilize the Student-Centered Learning (SCL) method, more than 80% actively participate in organizations and achieve accomplishments outside the academic field. In contrast, non-regular students, who are taught using conventional methods, do not gain any additional outputs beyond their work experience. Due to the monotonous nature of the conventional method, non-regular students tend to be passive listeners, resulting in a lack of interactivity. This study aims to describe students’ perceptions of the Student-Centered Learning and conventional methods in the Nursing Management course in the Bachelor of Nursing program at STIKES Dharma Husada. This research employs a descriptive historical approach with a retrospective study design. The sample consists of 87 students selected through purposive sampling. Data were collected using a questionnaire comprising 15 questions. Results The majority of regular students (67.1%) considered the SCL method effective, while 32.9% rated it as very effective. Among non-regular students, 90.9% found the method effective, and 9.1% considered it very effective. Overall, most students, both regular and non-regular (70.1%), perceived this learning method as very effective, while 32.9% rated it as effective. Conclusion and Recommendations Students’ perceptions of the Student-Centered Learning (SCL) method in the Nursing Management course at STIKES Dharma Husada indicate that most regular and non-regular students find this learning method effective. Future research should consider conducting further studies with similar sample characteristics and exploring the relationship between learning methods and perceptions of other nursing courses. For the Bachelor of Nursing program, it is recommended to simplify and develop learning methods to further enhance the quality of education, particularly in the Nursing Management course. Achievement of Sustainable Development Goals (SDGs) This study examines students' perceptions of the Student-Centered Learning (SCL) method in the Nursing Management course. This article contributes to SDG Goal 4, which aims to Ensure Inclusive and Equitable Quality Education and Promote Lifelong Learning Opportunities for All. Specifically, it aligns with Target 4.3, which, by 2030, seeks to ensure equal access for all women and men to affordable and quality technical, vocational, and higher education, including university education. Furthermore, the outcomes of this study can contribute to the achievement of SDG Goal 3 on ensuring healthy lives and promoting well-being for all at all ages.